The Effect of Workload on Employee Performance Through Work Stress as a Mediating Variable In Employees of PT Citilink Sultan Hasanuddin International Airport Makassar - Sabina, A. Zalza; Haeruddin, M. Ilham Wardhana; Burhanuddin, Burhanuddin; Musa, Muh. Ichwan; Syahrul, Khaidir; Mustafa, Muh. Yushar (Jurnal Riset Bisnis, Manajemen, dan Ilmu Ekonomi, 2025)
The approach used in this study is quantitative with descriptive and causal design. The population in this study includes individuals whose number is not known for certain. The sample was determined using the saturated or census sampling method, so that 45 respondents were obtained. Data collection was carried out through questionnaires, then analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) version 3.0 method. The results of the study indicate that: (1) Workload has a negative and significant effect on performance. (2) Workload has a positive and significant effect on work stress. (3) Work stress has a negative and significant effect on performance. (4) Work stress has a negative and significant effect in mediating the influence of workload on performance.